Dose distribution measurements using luminol water during irradiation of high-energy X-rays from medical linear accelerators (LINAC). (July 2023) - Yamamoto, Seiichi; Yamada, Koya; Yabe, Takuya; Hirano, Yoshiyuki; Kataoka, Jun
Abstract: Dose distribution measurements of high-energy X-rays from a medical linear accelerator (LINAC) in water are important for quality control (QC) of the system, and Cherenkov-light imaging is an efficient method for measuring the high-energy X-ray dose distribution. However, the depth profiles have an underestimated dose at increased depths due to the angular dependency of the Cherenkov light. Luminol water is a possible material for measuring the dose distribution by detecting the light emitted from the chemical reaction with the reactive hydroxyl radical ( ・ OH) produced in water by irradiation. In this study, we used luminol water for dose distribution measurements of high-energy X-rays from a LINAC. Imaging of the light emitted from luminol water was conducted using a cooled charge-coupled device (CCD) camera during irradiation with 6 MV X-rays from a LINAC to the luminol water. Imaging of the Cherenkov light in water was also conducted by irradiating 6 MV X-rays to water for correcting the Cerenkov-light component produced in luminol water. The Cherenkov-light image was subtracted from that of the luminol water to derive a dose image. The light emission of luminol water was ∼3 times higher than that of Cherenkov light in water. By subtracting the Cherenkov-light image from the luminol-water image, we could obtain an image that was identical to the dose distributions. The difference in the relative dose distribution was within −0.4% for the corrected image while that of the Cherenkov-light image was −7.9%. The multiple irradiations of luminol water with X-rays produced non-uniformity of emitted light, probably due to the production of hydrogen peroxide (H2 O2 ) in water. We confirmed that imaging luminol water was promising for dose distribution imaging by correcting the Cherenkov-light component in the images. The non-uniformity of the emitted light by multiple irradiations in luminol water needs to be solved for more stable measurements. Highlights: Light emission of luminol water was ∼3 times higher than that of Cherenkov light in water. By subtracting Cherenkov-light image, images identical to the dose could be measured. The difference in the relative dose distribution was within −0.4% for the corrected image. The multiple irradiations of luminol water with X-rays produced non-uniformity of images.